2021
DOI: 10.3390/foods10112827
|View full text |Cite
|
Sign up to set email alerts
|

From Plantation to Cup: Changes in Bioactive Compounds during Coffee Processing

Abstract: Coffee is consumed not just for its flavor, but also for its health advantages. The quality of coffee beverages is affected by a number of elements and a series of processes, including: the environment, cultivation, post-harvest, fermentation, storage, roasting, and brewing to produce a cup of coffee. The chemical components of coffee beans alter throughout this procedure. The purpose of this article is to present information about changes in chemical components and bioactive compounds in coffee during preharv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 130 publications
0
74
0
4
Order By: Relevance
“…These are capable of undergoing a nucleophilic addition to proteins e.g., thiol and free amino groups, thereby covalently modifying the proteins. The green coffee beans have been shown to possess polyphenol oxidase (PPO) activity [ 17 ]. Therefore, their proteins are liable to this type of modification [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are capable of undergoing a nucleophilic addition to proteins e.g., thiol and free amino groups, thereby covalently modifying the proteins. The green coffee beans have been shown to possess polyphenol oxidase (PPO) activity [ 17 ]. Therefore, their proteins are liable to this type of modification [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Rogers et al, only 1.1 and 0.2% of the amino acid content can be allocated to cysteine and methionine, respectively. Further, it was recently shown that the dry processing of the coffee beans may increase the content of the non-protein amino acid γ-aminobutyric acid [ 17 ]. In the soluble protein fraction of the 11S protein, glutamate and glutamine are the most abundant amino acids in coffee beans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, in medium roasts, a 60% loss of CGA has been observed and up to 100% loss in a dark roast. The optimal roasting condition for coffee is medium above which there is a significant reduction of bioactive compounds [50][51][52]. In general, the most studied CGAs in coffee are the three main CQA isomers, whereas diCQAs and FQAs have been barely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the efficacy varies, depending on the species, degree of roasting, brewing procedure, and decaffeination ( 45 ). Coffee varieties from various origins differ significantly in terms of their constituents, and multiple agricultural geography conditions of the coffee plant, such as the soil type, altitude, and harvest season, as well as the pre- and post-harvest management practices, influence coffee bean bioactivity ( 46 , 47 ).…”
Section: Introductionmentioning
confidence: 99%